DATA PREPARATION FOR WATER INJECTION LABORATORY TEST - Tjuwati Makmur; Nuraini Nuraini (Testing Center for Oil and Gas LEMIGAS, 2004)
Oil production limit that is usually followed by decrease of oil productivity in old fields is a major problem and can't be avoided. This case happened when cumulative oil production has approached primary recovery method. Decrease of the action of native reservoir energy is followed by drastically increase of production of water (saturation almost 100 %). In relation to this, a method is needed to obtain the additional oil recovery. Water injection method is one of the solutions to solve oil production problem that happened in old fields. It is expected that by using water injection method, productivity and oil recovery in old fields can be improved. Water that is used as the fluid injected into reservoir to improve oil recovery is sea water. How far oil recovery can be improved by using water injection method, is determined by a laboratory research. Before carrying out water injection laboratory test; one has to know what are the main points that play important role in determining the optimal oil recovery by water injection method. These are: firstly, basic parameters, secondly, laboratory test for water flooding, thirdly, the displacement of water injection process, then, standard operational procedure, next, water injection to obtain the additional oil recovey, lastly, the results are plotted a figure and or tabulated as the result of water injection laboratory test is obtained. In relation to the mentioned above, it will be better to write a scientific paper of water injection laboratory test. This paper is written based on our experience in enhanced oil recovery research (EOR), supported by textbook, such Ã¡s American Petroleum Institute, Petroleum Production Handbook and Standard Corrosion and water Technology For Petroleum Producers. Therefore, the main focus of this paper is